Teachers' embodied mitigation against allocating turns to unwilling students. Issue 4 (2nd October 2022) - Ishino, Mika
ABSTRACT: During teacher-centred classroom interaction, teachers often fail to solicit volunteer turn-takers. Even if students display their unwillingness to take a turn at the moment, teachers sometimes have no choice but to allocate them the turn, to move forward with the ongoing pedagogical activity. In such a moment, there can be a conflict between the students' autonomy in securing private time and the teacher's authority in forcing them to participate in the central activity. Paying special attention to such sensitive moments, this study explores how the teacher deals with them. The data for this study came from video recordings of English language classrooms in secondary education settings in Japan. Multimodal conversation analysis revealed that the teachers' particular embodied practice involves directing the gaze not towards the students but the notebook in their hands prior to turn allocation to a student. The teachers implemented this embodied practice in a sequentially recognisable manner. This practice allowed the teachers to mitigate their act of violating the classroom's social norm of 'allocating a turn to a willing speaker'. Based on the findings, this study discusses the classroom teacher's authority within the context of social relations with the students.